Oral presentation skills for engineering students : industry's criteria - Mohd Radzuan, Noor Raha (2010)
Today's world demands that engineers prepare themselves to rise to the challenges of the globalisation in the new millennium. To become global engineers, they need to acquire the soft skills on top of the hard skills. One of the important elements in soft skills is communication skills including presentation skills. In equipping Universiti Malaysia Pahang (UMP) engineering students for their professional world, oral presentation skills is one of the skills that is emphasized in our current English course syllabuses. It is believed that, being a successful and competitive engineer, one has to be excellent in both technical knowledge as well as formal oral presentations. Students must be able to communicate effectively using appropriate language and excellent features of presentation skills not only at academic setting, but also at workplace setting. Indeed, this skill is very important as there have been an increase number of communicative events in engineering profession. Being English educators, it is our concern to equip the engineering students with good formal oral presentation skills. This study aims 1) to discover the criteria for good project-based oral presentation from industry's perspective, 2) to identify the engineering lecturers' practice of oral presentation skills in their students 'Projek Sarjana Muda' (Final Project for Degree Students) presentation and finally 3) to propose a new marking scheme for project-based oral presentations that is aligned with industry's practice. Findings of research are gathered from documents from all the five engineering faculties in UMP and questionnaire distributed to the industry.